Design of Election Criminal Enforcement Through A Restorative Justice Approach in Nort Sumatra - Lubis, Muhammad Ansori; Syaputra, Muhammad Yusrizal Adi (Universitas Medan Area, 2024)
The large number of cases of suspected election crimes at every stage of the elections in Indonesia are not balanced with a fair law enforcement design and legal certainty. The establishment of the Integrated General Election Law Enforcement Center (Sentra Gakkumdu Pemilu) apparently did not have a significant impact in effectively prosecuting perpetrators of election crimes. This research aims to examine the design of law enforcement for election crimes and analyze the application of the concept of restorative justice as an approach to law enforcement for election crimes. The results of the research, firstly, are that the complexity of the law enforcement mechanism for election crimes causes the number of reports of election crimes submitted by the public to election supervisors to be meaningless. Second, that the current law enforcement design for election crimes still prioritizes punishment, even though law enforcement prioritizes the principle of ultimum remedium in its implementation. The absence of legal loopholes in prioritizing the concept of restorative justice in enforcing election criminal law is an obstacle for the Gakkumdu Center in enforcing election criminal law. The large number of cases of suspected election crimes that occur while the resolution time is relatively short makes it difficult for law enforcement to promote election crimes to promote justice and legal certainty. So there is a need to design technical regulations in implementing restorative justice in handling election crimes in the future.